Research and development of semi-automatic tomatomesh bag packing mechanism - Đặng Minh Phụng; Nguyễn Đăng Khoa (Journal of Technical Education Science, 2013)
Nowadays, the packing of tomatoes and other agricultural products in mesh bags is widely used in supermarkets trading agricultural products across the country. However, the packing is mainly carried out manually, which is accompanied with certain problems such as: time consumption, high costs and low productivity,leading to increased prices. Meanwhile, in Vietnam, studies on developing a tomato packing machine, especially those related to tomato mesh bag packingmachinehave not gained much interest. This paper presents the results of the research into semi-automatic tomato mesh bag packing mechanism, partly contributing to the packing mechanization and productivity improvementas well as meeting the increasing demand of the supermarkets trading agricultural products. Test results show that the semi-automatic tomato mesh bag packing mechanismworked well and the wires were firmly pressed, satisfying both safety and aesthetic requirements.